Impact of attention on rare events across industries in Indonesia - Dedi Hariyanto; Rayenda Khresna Brahmana; Wendy Wendy (Investment Management & Financial Innovations)
Rare events (RE) are substantial with significant impact but are difficult to predict, often deviating from regular expectations. These events trigger psychological reactions in the market and susceptible to irrational decisions that challenge logical assumptions. The rapidity of the crisis has led to highly volatile market conditions, fostering instances of asymmetric information. Therefore, this study aimed to explore the impact of attention on market dynamics by examining diverse possibilities over time. The article focused on all publicly listed industries on the Indonesian Stock Exchange (IDX/BEI). Using time series regression data from 1997 to 2020, the article comprised 5,615 observations across nine sectors. The primary model was based on three factors originating from the Fama-French and prospect theory, with attention serving as the main risk element to assess the impact of attention on abnormal returns (AR) during RE. The results disclosed that various events showed diverse effects on attention behavior, varying across all sectors. Additionally, moderation analysis showed a correlation between attention and AR. The results signified that RE mitigates the negative relationship between attention and AR. The adverse impact of attention on AR diminishes during RE. These results contributed to the literature by providing insights into the excessive attention to specific information disrupts market mechanisms, triggers disproportionate emotional responses, and alters investor preferences. Furthermore, this study established that events prompting excessive attention have varying effects on attention behavior across all sectors.